Anti-oxidant and hepatoprotective activities of total flavonoids of Indocalamus latifolius (Bangladesh Journal of Pharmacology, 2015)
The total flavonoids of Indocalamus latifolius were evaluated in term of their anti-oxidant and hepatoprotective activities. The results showed that in vitrohepatoprotective and anti-oxidant activities of total flavonoids at doses of 200 and 400 mg/kg and 100 mg/kg, respectively, were comparable to those of the known hepatoprotective drug silymarin at 100 mg/kg. These data were supplemented with histopathological studies of rat liver sections. Seven of the main flavonoid compounds purified by column chromatography using silica gel, sephadex LH-20 and develosil ODS, and determined to be vitexin, orientin, isovitexin, homoorientin, tricin, tricin-7-O-β-D-glucopyranoside and quercetin-3-O-glucopyranoside.